2002
DOI: 10.1192/bjp.180.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviours and attitudes following prolonged exposure to television among ethnic Fijian adolescent girls

Abstract: This naturalistic experiment suggests a negative impact of television upon disordered eating attitudes and behaviours in a media-naïve population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
273
1
13

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 518 publications
(304 citation statements)
references
References 22 publications
17
273
1
13
Order By: Relevance
“…We also observed that TV viewing was common in young generations. Becker et al (2002) investigated the effect of the primary introduction of TV among adolescents in a Fijian community and the consequent effect of TV viewing on traditional body aesthetic ideals. The major findings, which could be transposed to an urban Gambian setting, suggest that TV viewing quickly spreads western ideals and globalization creating an intergenerational conflict and 'hybrid identities' of young generations into the dominant culture.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that TV viewing was common in young generations. Becker et al (2002) investigated the effect of the primary introduction of TV among adolescents in a Fijian community and the consequent effect of TV viewing on traditional body aesthetic ideals. The major findings, which could be transposed to an urban Gambian setting, suggest that TV viewing quickly spreads western ideals and globalization creating an intergenerational conflict and 'hybrid identities' of young generations into the dominant culture.…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggest that it may be useful to distinguish between personal assimilation to changing cultural values and being situated in an acculturated milieu for future studies of the impact of acculturation on disordered eating and body image. Although previous research has suggested that intergenerational conflict may be associated with greater risk for disordered eating, 13,42,47 we could not identify studies that specifically investigated the impact of personal assimilation to a new cultural environment versus being situated in an acculturated milieu.…”
Section: Resultsmentioning
confidence: 94%
“…Recruitment of these cohorts and data collection have been described elsewhere. 13,32 Procedure and Assessments Data available from both cohorts included demographic information, height and weight, as well as responses to the Questionnaire on Eating and Weight Patterns-Revised (QEWP-R; see Refs. [33][34][35][36] and to a selfreport measure developed for an ethnic Fijian population that included items relating to body shape concern, eating attitudes, and adherence to traditional Fijian cultural values and practices.…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations